Light-emitting element and display device
By using the base material of an inorganic compound and quantum dots in the light emitting layer of the light emitting element, and setting it between the hole transport layer and the light emitting layer, combined with the technology of doping the second group VI element, the problems of excessive electrons and insufficient holes are solved, and the reliability and luminous characteristics of the light emitting element are improved.
Patent Information
- Application Number
- CN202280098831.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-29
- Publication Date
- 2025-03-18
AI Technical Summary
In the conventional light emitting elements, the amount of electron injection is larger than the amount of hole injection, which leads to excessive electrons and insufficient holes, and the organic ligand is prone to deterioration, reducing reliability.
The base material containing an inorganic compound and a quantum dot are introduced into the light emitting layer, and arranged between the hole transport layer and the light emitting layer. By doping the second group VI elements, the carrier balance between the hole and electron is improved.
The reliability of the light emitting element is improved, the carrier balance between holes and electrons is improved, and the luminous characteristics are optimized.
Smart Images

Figure CN119654967A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a light emitting element and a display device. Background Art
[0002] In a light-emitting element using quantum dots as a light-emitting material in a light-emitting layer, generally speaking, the amount of electrons injected in the light-emitting layer is greater than the amount of holes injected. In the past, excessive electron supply and insufficient holes became a problem. In addition, generally speaking, organic ligands are used on the surface of quantum dots for the purpose of protecting quantum dots and improving the dispersibility of solvents. However, organic ligands composed of organic matter are easily degraded, resulting in reduced reliability.
[0003] Non-Patent Document 1 discloses quantum dots protected with sulfides instead of organic ligands. By inorganicizing the light-emitting layer by protecting the quantum dots with sulfides, organic substances that are easily degraded can be eliminated, thereby improving reliability. Prior art literature Non-patent literature
[0004] Non-patent literature 1: InP-Quantum-Dot-in-ZnS-Matrix Solids for Thermal and Air Stability, Chemical Material, 2020, 32, 22, 9584-9590 Summary of the invention Technical problems to be solved by the present disclosure
[0005] However, even if the light-emitting layer is made inorganic, there is still an excess of electrons.
[0006] One aspect of the present disclosure has been made in view of the above-mentioned problems, and an object thereof is to provide a light-emitting element and a display device that are highly reliable, can improve the carrier balance between holes and electrons, and have excellent light-emitting characteristics. Technical solutions for solving technical problems
[0007] In order to solve the above-mentioned problems, a light-emitting element of one embodiment of the present disclosure comprises: a light-emitting layer; and a hole transport layer, which is arranged adjacent to the light-emitting layer, wherein the light-emitting layer comprises a matrix and a plurality of quantum dots, wherein the matrix contains at least one inorganic compound, wherein the matrix comprises a matrix compound as the inorganic compound, wherein the matrix compound has at least one first VI group element as a main component, and wherein the matrix comprises at least one second VI group element, wherein the period number of the second VI group element is smaller than the period number of the first VI group element contained in the matrix compound, and wherein the concentration of the sum of the second VI group elements in the matrix is within 1×10 16 Atom / cm 3 Above and 1×10 20Atom / cm 3 Within the following range.
[0008] In order to solve the above-mentioned problems, a display device according to one aspect of the present disclosure includes the above-mentioned light-emitting element according to one aspect of the present disclosure. Beneficial Effects
[0009] According to one embodiment of the present disclosure, it is possible to provide a light-emitting element and a display device that have high reliability, can improve the carrier balance between holes and electrons, and have excellent light-emitting characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 It is a cross-sectional view schematically showing the structure of the light emitting element according to the first embodiment. Figure 2 Yes means Figure 1 A cross-sectional view showing an example of a schematic structure of a quantum dot and its vicinity in a light-emitting element shown. Figure 3 It means in Figure 1 A cross-sectional view showing a state in which adjacent quantum dots are close to each other in a light-emitting element shown. Figure 4 Yes means Figure 1 FIG. 1 is a schematic diagram showing an example of the band structure of each functional layer when each functional layer between the anode and the cathode in the light-emitting element is in an isolated state. Figure 5 It means that Figure 4 The illustrated diagram is a schematic diagram of an example of the band structure of each functional layer in a state where each functional layer is bonded and band-shifted so that the Fermi levels are aligned. Figure 6 This is a schematic diagram showing an example of the band structure of each functional layer when each functional layer between the anode and the cathode in a comparative light-emitting element is in an isolated state. Figure 7 It means that Figure 6 The illustrated diagram is a schematic diagram of an example of the band structure of each functional layer in a state where each functional layer is bonded and band-shifted so that the Fermi levels are aligned. Figure 8 It is a graph showing the JV characteristics of the light emitting element of the first embodiment and the JV characteristics of a comparative light emitting element together. Fig. 9 It is a graph showing the light emitting characteristics of the light emitting element of the first embodiment and the light emitting characteristics of a comparative light emitting element together. Fig.10 This is another graph showing the light emitting characteristics of the light emitting element of the first embodiment and the light emitting characteristics of a comparative light emitting element together. Fig.11This is a flowchart showing an example of a method for manufacturing the light emitting element according to the first embodiment. Fig.12 It is used to illustrate Fig.11 A cross-sectional schematic diagram of the ligand replacement step is shown. Fig.13 This is a cross-sectional view showing a schematic structure of a quantum dot dispersion liquid for forming the light-emitting element of the first embodiment. Fig.14 It is a cross-sectional view showing a process of an example of a method for forming a light-emitting layer of the light-emitting element of the first embodiment. Fig.15 It is a cross-sectional view schematically showing the structure of a light emitting element according to a second embodiment. Fig.16 It means in Fig.15 This is a schematic diagram showing an example of the band structure of each functional layer when the second VI group element is mixed only in the first part of the first light-emitting layer in the light-emitting element shown and each functional layer between the anode and the cathode is in an isolated state. Fig.17 It means that Fig.16 The illustrated diagram is a schematic diagram of an example of the band structure of each functional layer in a state where each functional layer is bonded and band-shifted so that the Fermi levels are aligned. Fig.18 This is a cross-sectional view showing an example of a schematic configuration of a light emitting element according to a modification of the second embodiment. Fig.19 It is a plan view showing a configuration example of a display device according to a third embodiment. DETAILED DESCRIPTION
[0011] [First embodiment] Hereinafter, one embodiment of the present disclosure will be described in detail. In addition, in the following, the description of "A to B" for two numbers A and B means "A or more and B or less" unless otherwise specified. In addition, in the following, a layer formed by a process before the layer of the comparison object is referred to as a "lower layer", and a layer formed by a process after the layer of the comparison object is referred to as an "upper layer".
[0012] In addition, in the present disclosure, "organic material" or "organic compound" means a substance in which carbon is the center of an atomic bond, and "inorganic material" or "inorganic compound" means a substance other than an organic substance. Therefore, in the present disclosure, the so-called "inorganic material" or "inorganic compound" is considered to mean a substance in which carbon is not included in an atomic bond. In addition, it can also be a substance in which carbon is not included in the center of an atomic bond. Moreover, it is not excluded that a substance is considered to have no carbon chain.
[0013] In addition, for the sake of convenience, the components having the same functions as the components described previously are marked with the same reference numerals below, and their description is not repeated. In the embodiments described later, the differences from the embodiments described previously are described. Unless otherwise specified, the same deformation as the embodiments described previously can of course be performed.
[0014] (Schematic Structure of Light Emitting Element) The light-emitting element of this embodiment includes a light-emitting layer and a hole transport layer provided adjacent to the light-emitting layer, wherein the light-emitting layer includes a base material containing at least one inorganic compound and a plurality of quantum dots.
[0015] Hereinafter, the above-mentioned light-emitting element has a conventional structure in which the anode is used as the lower electrode and the cathode is used as the upper electrode, and a hole transport layer, a light-emitting layer, and an electron transport layer are provided between the anode and the cathode as functional layers. In addition, in the present disclosure, the layers between the anode and the cathode are collectively referred to as functional layers.
[0016] However, the light emitting element of this embodiment is not limited thereto, and as a functional layer, it is sufficient to have a light emitting layer and a hole transport layer disposed adjacent to the light emitting layer. In addition, the light emitting element of this embodiment may also have an inverted structure with a cathode as a lower electrode and an anode as an upper electrode.
[0017] Hereinafter, the light-emitting layer may be referred to as “EML”, the hole transport layer may be referred to as “HTL”, and the electron transport layer may be referred to as “ETL”. In addition, the quantum dot may be referred to as “QD”.
[0018] Figure 1 It is a cross-sectional view showing a schematic structure of the light emitting element 2 according to the present embodiment. Figure 2 Yes means Figure 1 The cross-sectional view is a schematic diagram of an example of the structure of QD 14 and its vicinity in the light emitting element 2 shown. Figure 3 Yes means Figure 1 The cross-sectional view of the light emitting element 2 is shown in a state where adjacent QDs 14 are close to each other.
[0019] like Figure 1As shown, as an example, the light-emitting element 2 of this embodiment has a structure in which an anode 4, HTL6, EML8, ETL10 and a cathode 12 are sequentially arranged from the lower layer side (for example, the side of a support body not shown such as a substrate). Each layer from the anode 4 to the cathode 12 is usually supported by a substrate as a support body. In addition, although the illustration and description are omitted, the light-emitting element 2 may also have a functional layer other than HTL6, EML8 and ETL10 not shown between the anode 4 and the cathode 12. As an example, for example, the light-emitting element 2 may also be provided with a hole injection layer having a hole transport property and promoting the injection of holes from the anode 4 to the HTL6 between the anode 4 and the HTL6. In addition, the hole injection layer is sometimes referred to as "HIL" below.
[0020] At least one of the anode 4 and the cathode 12 is a light-transmitting electrode. In addition, either the anode 4 or the cathode 12 may be a so-called reflective electrode having light reflectivity. The light-emitting element 2 can extract light from the light-transmitting electrode side.
[0021] For example, when the light emitting element 2 is a top emission type light emitting element that emits light from the upper electrode side, a light-transmitting electrode is used for the upper electrode, and a reflective electrode is used for the lower electrode. On the other hand, when the light emitting element 2 is a bottom emission type light emitting element that emits light from the lower electrode side, a light-transmitting electrode is used for the lower electrode, and a reflective electrode is used for the upper electrode.
[0022] The light-transmitting electrode uses a conductive material that transmits visible light, such as ITO (indium tin oxide), IZO (indium zinc oxide), ZnO, AZO (also known as aluminum-doped zinc oxide, ZAO), BZO (boron-doped zinc oxide) or FTO (fluorine-doped tin oxide).
[0023] For the reflective electrode, it is preferable to use a conductive material having a high reflectivity of visible light, such as a metal such as Al, Cu, Au, Ag, or MgAg, or an alloy containing these metals.
[0024] HTL6 contains a hole transporting material and has a function of injecting holes (h + , refer to the following Figure 5 ) is transported to the charge transport layer having hole transport function of EML 8. As the hole transport material, organic materials or inorganic materials used in light-emitting elements including QD, i.e., QLED (quantum dot light-emitting diode) or OLED (organic light-emitting diode) can be used.
[0025] As organic materials for HTL6, for example, conductive compounds such as 4,4'-bis(carbazole-9-yl)biphenyl (CBP), polyphenylene vinylene (PPV), a composite of poly(3,4-ethylenedioxythiophene) (PEDOT) and polystyrene sulfonic acid (PSS) (PEDOT:PSS), poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-4-sec-butylphenyl)diphenylamine)) (TFB), or polyvinylcarbazole (PVK) can be used.
[0026] As the inorganic material of HTL6, for example, metal oxides such as molybdenum oxide, NiO, Cr2O3, MgO, MgZnO, LaNiO3, or WO3 can be used. In particular, as the material of HTL6, a material having a large electron affinity and ionization potential is preferred.
[0027] The ETL 10 is a charge transport layer having an electron transport function. The charge transport layer contains an electron transport material and transports electrons (e) injected from the cathode 12. - For example, refer to the following Figure 5 ) is transported to the EML 8. As the electron transport material, for example, in addition to TiO 2 , an organic material or an inorganic material conventionally used in QLED or OLED can also be used.
[0028] As an organic material of the ETL 10, a conductive compound such as tris(8-hydroxyquinoline)aluminum complex (Alq3), bathocuproine (BCP), or 2-(4′-biphenyl)-5-(4″-tert-butylphenyl)-1,3,4-oxadiazole (t-Bu-PBD) can be used.
[0029] As the inorganic material of the ETL 10, for example, ZnO, AZO, ITO, In-Ga-Zn-O semiconductor (for example, indium gallium zinc oxide) or metal oxides such as electron compounds can be used. In particular, as the material of the ETL 10, a material with low electron affinity is preferred.
[0030] EML 8 includes a matrix 16 containing at least one inorganic compound and a plurality of QDs 14. In the present disclosure, removing the organic ligand and embedding the QDs 14 into the matrix 16 containing the above-mentioned inorganic compound is referred to as inorganicizing EML 8. In addition, EML 8 including the matrix 16 containing the above-mentioned inorganic compound is sometimes referred to as inorganicized EML 8.
[0031] In EML 8, holes transported from anode 4 and electrons transported from cathode 12 recombine, and excitons generated thereby transfer from the conduction band energy level to the valence band energy level of QD 14 to emit light. EML 8 includes nano-sized QD 14 corresponding to the emission color as a light emitting material.
[0032] QD14 is a point where the maximum width of a particle is below 100 nm. Generally speaking, the composition of QD14 is derived from a semiconductor material, and is therefore sometimes referred to as a semiconductor nanoparticle. In addition, the composition of QD14 is usually derived from an inorganic material, and is therefore sometimes referred to as an inorganic nanoparticle. In addition, the composition of QD14, for example, has a specific crystal structure, and is therefore sometimes referred to as a nanocrystal.
[0033] The shape of QD14 is not particularly limited as long as it is within the range that satisfies the above-mentioned maximum width, and is not limited to a spherical three-dimensional shape (circular cross-sectional shape). For example, it can be a polygonal cross-sectional shape, a rod-shaped three-dimensional shape, a branch-shaped three-dimensional shape, a three-dimensional shape with concave and convex surfaces, or a combination of these shapes.
[0034] QD14 may include at least one metal element. Examples of the metal element included in QD14 include Cd, Zn, In, Sb, Al, Si, Ga, Pb, Ge, and Mg. In addition, QD14 may be a semiconductor material formed by combining at least one metal element with a non-metal element such as S, Te, Se, N, P, and As.
[0035] QD14 can be formed by only the nucleus, or can be a two-component nucleus, a three-component nucleus, or a four-component nucleus. Figure 2 As shown, QD 14 may have a core-shell structure including a core 14C and a shell 14S, or may be a core-shell type or a core-multi-shell type.
[0036] like Figure 2 As shown, in the case where QD14 includes a shell 14S, there is a core 14C in the center, and the shell 14S only needs to be arranged on the surface of the core 14C. The shell 14S preferably covers the entire core 14C, but the shell 14S does not need to completely cover the core 14C. The shell 14S can also be formed on a portion of the surface of the core 14C. For QD14, if it is judged that a shell 14S is formed on a portion of the surface of the core 14C in the observation on a cross section of the QD14, or it is judged that the shell 14S wraps the core 14C, it can be said that it has a core-shell structure. Therefore, it is sufficient as long as it can be judged that the shell 14S covers the entire core 14C by observing a cross section of QD14. In addition, the above-mentioned cross-sectional observation can be performed, for example, by a scanning transmission electron microscope (STEM) or a transmission electron microscope (TEM).
[0037] In addition, QD 14 may include doped nanoparticles, or may have a structure with a gradient composition. In addition, shell 14S may be formed in a state of being solid-solution-coated on the surface of core 14C. Figure 2In FIG. 1 , the boundary between the core 14C and the shell 14S is indicated by a dotted line, but this may or may not be confirmed by analysis. The shell 14S may also be formed into multiple layers.
[0038] QD14 may also include the core material of QD and the materials used in the shell material in the respective materials of the core 14C and the shell 14S. The core 14C may be composed of Si, Ge, CdSe, CdS, CdTe, InP, GaP, InN, ZnSe, ZnS, ZnTe, CdSeTe, GaInP, ZnSeTe, etc. The shell 14S may be composed of CdS, ZnS, CdSSe, CdTeSe, CdSTe, ZnSSe, ZnSTe, ZnTeSe, AIP, etc. As an example, when the shell 14S includes ZnSSe, the ZnSSe included in the shell 14S may also be ZnS x Se 1-x (0≤x≤1). When QD14 has a core-shell structure, an example of the material of QD14 (combination of core 14C / shell 14S materials) includes ZnSe / ZnS, InP / ZnS, CdSe / CdS, CdSe / ZnSe, CIGS / ZnS, and the like.
[0039] In addition, the composition represented by the chemical formula in the present disclosure is preferably stoichiometric, but it does not exclude cases other than stoichiometric.
[0040] QD14 can change the emission wavelength in various ways depending on the particle size, composition, etc. QD14 is a QD that emits visible light, and by appropriately adjusting the particle size and composition of QD14, the emission wavelength can be controlled within the blue to red wavelength range.
[0041] The core 14C of QD14 has a valence band energy level and a conduction band energy level, and is a luminescent material that emits light by recombination of holes in the valence band energy level and electrons in the conduction band energy level. Since the light emitted from QD14 has a narrow spectrum due to the quantum confinement effect, light with a deeper chromaticity can be obtained.
[0042] In addition, QD14 in EML8 does not need to be Figure 1 QD14 may be arranged regularly as shown in FIG. 8 , or may be included in EML8 in an unordered manner. Figure 1 As shown in FIG. 1 , a state is formed between adjacent QDs 14 where the base material 16 and QDs 14 are not close to each other. Figure 3As shown, the EML 8 may include two or more QDs 14 close to each other. The thickness of the EML 8 may be about 1 nm to about 100 nm, preferably about 10 nm to about 60 nm.
[0043] In addition, in the present disclosure, the matrix refers to a component that contains other substances and holds them, and can be called a base material, a substrate, or a filling material. That is, in the present disclosure, the matrix 16 refers to a component that contains QDs 14 and holds them. The matrix 16 is an element that constitutes the film in which QDs 14 are distributed, such as Figure 1 The figure shows one of the components of the EML 8 including a plurality of QDs 14. In addition, the base material 16 may be solid at room temperature.
[0044] The matrix 16 can be filled in the EML 8. Figure 1 As shown, two QDs 14 among the plurality of QDs 14 may be focused on, and the matrix 16 fills the space between the two QDs 14 (i.e., the region Y (space) between the two QDs 14). If the two QDs are set as the first QD 14a and the second QD 14b, the region Y is a region surrounded by two straight lines (common external tangent lines) connected to the peripheries of the first QD 14a and the second QD 14b and the relative peripheries of the first QD 14a and the second QD 14b in cross-sectional observation.
[0045] In addition, Figure 1 In the example, the QD 14 is buried in the base material 16 at intervals. However, as described above, in the EML 8, the adjacent QDs 14 may be not close to each other, or may be close to each other. Figure 3 As shown, even if the adjacent first QD 14a and second QD 14b are close to each other, there can be a region Y (space) between these first QD 14a and second QD 14b. Even if these first QD 14a and second QD 14b are close to each other, the matrix 16 can fill the region Y (space) between these first QD 14a and second QD 14b.
[0046] Therefore, in EML8, the matrix 16 can fill the area (space) outside the QD14. Therefore, in EML8, the matrix 16 can also fill the area (space) outside the QD14. EML8 can have a QD group (quantum dot group) including a plurality of QD14, and the matrix 16 can fill the area (space) outside the QD group of EML8. Here, more than three QD14 are collectively referred to as a QD group. In EML8, the matrix 16 can fill the area (space) outside the plurality of QD14. The outer edge (upper surface and lower surface) of EML8 can also be covered by the matrix 16. In addition, it can also be configured that there is a portion of the matrix 16 from the outer edge of EML8, and QD14 is located at a position away from the outer edge of EML8. The outer edge of EML8 can also be formed not only by the matrix 16, but also by a portion of QD14 exposed from the matrix 16. In EML8, the matrix 16 can represent a portion other than QD14.
[0047] The matrix 16 may contain a plurality of QDs 14. The matrix 16 may be formed so as to fill spaces between the plurality of QDs 14 (ie, spaces formed between the plurality of QDs 14). The matrix 16 may also partially or completely fill spaces between the plurality of QDs 14.
[0048] The base material 16 may include a 1000 nm thick layer along a plane direction perpendicular to the layer thickness direction. 2 The continuous film refers to a film that is not separated on one plane by materials other than the material constituting the continuous film. The continuous film may also be an integrated film that is continuously connected by chemical bonds of the materials constituting the base material 16.
[0049] The base material 16 may include the same material as the shells 14S included in each of the plurality of QDs 14. In other words, the shells 14S may include the same material as the parent compound of the base material 16. When the shells 14S include the same material as the parent compound of the base material 16, the shells 14S are continuously connected to the parent compound of the base material 16, and thus the quality of the base material 16 can be improved.
[0050] Thus, when the base material 16 includes the same material as the shell 14S, the average distance between adjacent cores 14C (inter-core distance) can be more than 3 nm, or more than 5 nm, so as to avoid contact between QD14 and avoid agglomeration of QD14. Alternatively, the average distance between adjacent cores 14C can be more than 0.5 times the average core diameter. The inter-core distance is obtained by averaging the distances between adjacent cores in a space containing 20 cores. The inter-core distance can be kept wider than the distance when the shells 14S are in contact with each other. The average core diameter is the diameter after averaging the core diameters of 20 cores 14C in a cross-sectional observation in a space containing 20 cores. The core diameter can be set to the diameter of a circle with the same area as the core area in a cross-sectional observation.
[0051] The concentration of the matrix 16 in the EML8 is, for example, the area ratio of the matrix 16 in the cross section of the EML8. In the cross-sectional observation of the EML8, the concentration of the matrix 16 can be greater than 10% and less than 90%, or greater than 30% and less than 70%. The concentration of the matrix 16 can be measured, for example, based on the area ratio in the image processing in the cross-sectional observation of the EML8. In the case where the QD14 is a core-shell structure, the concentration of the shell 14S can be greater than 1% and less than 50%. The shell 14S and the matrix 16 are composed of the same material (same composition), and when the shell 14S and the matrix 16 cannot be distinguished, the concentration of the total area of the shell 14S and the matrix 16 can be in the numerical range after adding the numerical range of the concentration of the matrix 16 to the numerical range of the concentration of the shell 14S. The ratio of the core 14C of the QD14 to the shell 14S and the matrix 16 can be adjusted so that their total is appropriately less than 100%. In this way, when the shell 14S and the base material 16 cannot be distinguished, the shell 14S may be regarded as a part of the base material 16 .
[0052] The EML 8 may be composed of a plurality of QDs 14 and a base material 16. When analyzing the EML 8, the intensity of carbon detected by the chain structure may be less than the noise.
[0053] The constituent material of the matrix 16 preferably has a wider band gap (hereinafter referred to as "Eg") than the constituent material of the QD 14. For example, as described above, when the QD 14 has the core 14C and the shell 14S, the Eg of the matrix 16 is preferably larger than the Eg of the core 14C or the shell 14S.
[0054] The recombination of carriers (electrons and holes) injected into QD14 is mainly generated in the core 14C. The shell 14S has the function of suppressing the generation of defects or dangling bonds in the core 14C and reducing the recombination of carriers that have undergone the deactivation process. When the Eg of the base material 16 is greater than the Eg of the core 14C or the shell 14S, the exciton has a high restriction effect on the core 14C, and the recombination of carriers in the core 14C or the excitons generated by light absorption are difficult to diffuse to the base material 16, which can improve the luminous efficiency of the light-emitting element 2.
[0055] In addition, as long as the Eg of the matrix 16 is greater than the Eg of the core 14C, it may be the same as or less than the Eg of the shell 14S. However, the Eg of the matrix 16 is preferably greater than the Eg of the shell 14S. In this case, the exciton has a higher confinement effect on the core 14C, and the diffusion of the exciton from the QD 14 to the matrix 16 can be suppressed, which can further improve the luminous efficiency.
[0056] The matrix 16 contains at least one inorganic compound. The inorganic compound (inorganic material) constituting the matrix 16 may be a semiconductor material or an insulating material.
[0057] In addition, the base material 16 only needs to be a main material of an inorganic compound, and the case where a material different from the inorganic compound used in the main material is added as an additive is not excluded.
[0058] The matrix 16 includes, as the inorganic compound, a matrix compound having at least one Group VI element (first Group VI element) as a main component and a Group VI element (second Group VI element) having a period number smaller than that of the first Group VI element. In addition, the matrix 16 may also contain a substance different from the matrix compound as, for example, an additive.
[0059] In the present disclosure, the marking of the group number of the element using Roman numerals is based on the marking of the old IUPAC method, and the VI group elements include the VIA group elements and the VIB group elements. Therefore, based on the marking of the new IUPAC method, the so-called VI group elements are the 6 group elements and the 16 group elements. In the present disclosure, the marking of the group number of the element using Arabic numerals represents the marking based on the new IUPAC method. The group number in the old IUPAC method is consistent with the valence electron number of the form.
[0060] Specifically, the VIA group elements include Cr (chromium), Mo (molybdenum), W (tungsten), Sg (gold), As the VIB group elements, specifically, in order of smaller period numbers, O (oxygen), S (sulfur), Se (selenium), Te (tellurium), Po (polonium), and Lv (leverium) can be cited. In addition, O belongs to the second period, S belongs to the third period, Cr and Se belong to the fourth period, Mo and Te belong to the fifth period, W and Po belong to the sixth period, and Sg and Lv belong to the seventh period.
[0061] When the first Group VI element belongs to the m-th period (m represents an integer of 2 or more), the second Group VI element uses a Group VI element belonging to the mk-th period (k represents an integer of 1 or more and m-1 or less).
[0062] The parent compound is preferably a Group II-VI compound. Group II elements include Group IIA elements and Group IIB elements, and refer to Group 2 elements and Group 12 elements. In the present disclosure, the Group II-VI compound may contain Group II elements and Group VI elements in a composition ratio of about 1:1, or may contain Group VI elements in a ratio of more than 1:1 relative to Group II elements. That is, the parent compound may contain a Group II-VI compound with an excess of Group VI elements.
[0063] Examples of the parent compound include compounds containing one or more Group II elements selected from magnesium (Mg), zinc (Zn), cadmium (Cd) and mercury (Hg), and one or more Group VI elements selected from O, S, Se and Te.
[0064] In order to maintain or strengthen the restriction of the exciton on the core 14C of QD14, as described above, the parent compound preferably has an Eg that is equal to or wider than the core 14C or shell 14S of QD14, and more preferably has an Eg that is equal to or wider than the shell 14S. In addition, in order to make the quality of the matrix 16 good, the shell 14S of QD14 is preferably continuously connected to the crystal of the matrix 16. Alternatively, the shell 14S of QD14 and the matrix 16 can also be formed by amorphous. Therefore, as the above-mentioned matrix compound, it is preferably a II-VI group compound used in the shell of a conventional QD, and in the matrix 16, especially the matrix compound, it is preferred to use the same material as the shell 14S of QD14.
[0065] As the first group VI element, any group VI element other than O can be used, but it is preferably at least one selected from the group consisting of S, Se and Te. Among the II-VI compounds, S, Se and Te are generally used for the shell of QD and are particularly suitable as parent compounds. In addition, as described above, the parent material 16 includes a parent compound having at least one first group VI element as a main component, and includes a second group VI element having a smaller period number than the first group VI element. O is removed from the first group VI elements because it has the smallest period number among the group VI elements.
[0066] Examples of II-VI group compounds include magnesium sulfide (MgS), magnesium selenide (MgSe), zinc sulfide (ZnS), zinc selenide (ZnSe), zinc telluride (ZnTe), cadmium selenide (CdSe), cadmium telluride (CdTe), mercury sulfide (HgS), mercury selenide (HgSe), mercury telluride (HgTe), cadmium sulfide selenide (CdSeS), cadmium telluride selenide (CdSeTe), cadmium telluride sulfur (CdSTe), zinc sulfide (ZnSeS), zinc telluride selenide (ZnSeTe), zinc telluride sulfide (ZnTeS), mercury sulfide selenide (HgSeS), mercury telluride sulfur (HgSeTe), cadmium zinc sulfide (CdZnS), cadmium zinc selenide (CdZnS), and cadmium zinc selenide (CdZnS). Se), cadmium zinc telluride (CdZnTe), cadmium mercury sulfide (CdHgS), cadmium mercury selenide (CdHgSe), cadmium mercury telluride (CdHgTe), mercury zinc sulfide (HgZnS), mercury zinc selenide (HgZnTe), magnesium zinc selenide (MgZnSe), magnesium zinc sulfide (MgZnS), cadmium zinc sulfide selenide (CdZnSeS), cadmium zinc telluride selenide (CdZnSeTe), cadmium zinc telluride sulfur (CdZnSTe), cadmium mercury sulfide selenide (CdHgSeS), cadmium mercury selenide (CdHgSeTe), cadmium mercury sulfur (CdHgSTe), mercury zinc sulfide selenide (HgZnSeS), mercury zinc telluride selenide (HgZnSeTe), mercury zinc telluride sulfur (HgZnSTe), and mixtures thereof. Thus, II-VI compounds are not limited to binary systems, but may also be ternary or quaternary compounds. In addition, the chemical formula recorded in brackets after the compound name is a representative example. In addition, as described above, the composition ratio recorded in the chemical formula is ideal as long as the composition of the actual compound is stoichiometric as in the chemical formula, but it may not be stoichiometric.
[0067] As shown in the above examples, the II-VI compound used in the above-mentioned parent compound may contain, for example, metal sulfide. In particular, shell 14S is mostly ZnS. As described above, the parent compound preferably uses the same material as shell 14S of QD14. Therefore, when shell 14S is ZnS, ZnS is preferably used as the parent compound. The band gap of ZnS is 3.6 eV.
[0068] However, the present embodiment is not limited thereto. Generally speaking, in the shell of QD, a metal sulfide containing a metal element M other than Zn, such as ZnMS, is also preferably used as ZnS. Therefore, as the II-VI group compound used for the above-mentioned parent compound, a metal sulfide containing a metal element M other than Zn, such as ZnMS, may also be used. The above-mentioned metal element M is preferably Mg, Li, etc., which is higher than Zn in the periodic table.
[0069] Thus, the base material 16 may be a mixed crystal of a metal sulfide containing a first element and a metal sulfide containing a second element, or may be a mixed crystal abc in which a compound ac composed of an element a and an element c is mixed with a compound bc composed of an element b and an element c. When the base material 16 includes a mixed crystal of a metal sulfide containing a first element and a metal sulfide containing a second element as a base compound, for example, the first element is Zn and the second element is Mg or Li (lithium).
[0070] In this way, the base material 16 can contain Mg or Li, or Mg and Li. Mg and Li belong to the upper period with a period number smaller than Zn. Therefore, if either or both of Mg and Li are contained at the composition level, the Eg of the base material 16 is expanded, and the current flowing outside the QD 14 is suppressed. Therefore, by including at least one of Mg and Li in the base material 16, the injection efficiency of holes into the QD 14 can be improved, and the luminous efficiency can be further improved.
[0071] These Mg and Li are preferably contained in the base material 16 at the composition level. In other words, these Mg and Li preferably constitute a part of the composition of the base material 16. Therefore, when the base material 16 contains at least one of Mg and Li, the lower limit of the total concentration of Mg and Li contained in the base material 16 is preferably 1×10 21 Atom / cm 3 On the other hand, when the base material 16 includes, for example, a mixed crystal ZnMgS of ZnS and MgS, or a mixed crystal ZnLiS of ZnS and LiS, the crystal system of MgS and LiS is different from that of ZnS, and therefore, the upper limit of the total composition of Mg or Li or Mg and Li in the ZnS base in the base material 16 is 10%. Therefore, when converted into concentration, when the base material 16 includes at least one of Mg and Li, the upper limit of the total concentration of Mg and Li contained in the base material 16 becomes 1×10 22 Atom / cm 3 Therefore, when the base material 16 contains at least one of Mg and Li, the total concentration of Mg and Li contained in the base material 16 is preferably 1×10 21 Atom / cm 3 Above and 1×10 22 Atom / cm 3 the following.
[0072] The second VI group element is mixed (doped) into the parent compound as an impurity element (additive), and the total concentration of the second VI group element in the parent material 16 is 1×10 16 Atom / cm 3 Above and 1×10 20 Atom / cm 3 Within the following range.
[0073] As mentioned above, the second VI group element uses a VI group element with a smaller periodic number than the first VI group element. Therefore, in the case where the parent compound is, for example, ZnS as described above, since S as a VI group element belongs to the third period, as the second VI group element, O, a VI group element belonging to the second period, is used. In this case, the parent material 16 contains S and O, two VI group elements, as VI group elements. In addition, of course, in the case where the first VI group element is, for example, Se belonging to the fourth period, the second VI group element can be O belonging to the second period, or S belonging to the third period. In this case, the parent material 16 can contain Se and S, or Se and O, two VI group elements, as VI group elements, or it can contain Se, S and O, three VI group elements. In addition, in the case where the first VI group element is, for example, Te belonging to the fifth period, the second VI group element can be O belonging to the second period, S belonging to the third period, or Se belonging to the fourth period. In this case, the base material 16 may contain two Group VI elements of Te and Se, Te and S, or Te and O as Group VI elements, or may contain three Group VI elements of Te, Se and S, or Te, Se and O, or Te, S and O. Furthermore, when the first Group VI element is, for example, Te belonging to the fifth period, the base material 16 may contain three Group VI elements of Te, Se and S, or Te, Se and O, or Te, S and O, or may contain four Group VI elements of Te, Se, S and O.
[0074] The second Group VI element is not particularly limited as long as it is a Group VI element with a period number smaller than that of the first Group VI element. As described above, the base material 16 only needs to contain the first Group VI element and the second Group VI element, and may contain three or more Group VI elements as long as it contains two or more Group VI elements.
[0075] In addition, the structure of the base material 16 is only required to be observed with a width of about 100 nm in the cross-sectional observation of the EML 8 to understand that it is the above-mentioned structure, and it is not necessary to observe the above-mentioned structure in the entire EML 8.
[0076] When a foreign element of the same group as the constituent element of the parent compound (i.e., the same group of the periodic table) and having a smaller period number than the constituent element is mixed (doped) into the base material 16 as an impurity element, a part of the constituent element of the parent compound is replaced by the foreign element. In other words, when a foreign element having the same valence electron configuration as the constituent element of the parent compound and having a large electronegativity indicating the ease of attracting electrons (in other words, a small ion radius) is mixed into the base material 16, a part of the constituent element is replaced by the foreign element.
[0077] Therefore, if a second group VI element higher than the first group VI element contained in the parent compound by more than one period is mixed into the parent material 16, a part of the first group VI element contained in the parent compound is replaced by the second group VI element. Since the period number of the second group VI element is smaller than that of the first group VI element, it has a valence electron orbit equivalent to the first group VI element of the parent compound and the same number of valence electrons, and its electronegativity is greater than that of the first group VI element, and its ion radius is smaller than that of the first group VI element. Therefore, even if the second group VI element is mixed into the parent material 16, it maintains electrical neutrality and the conduction type does not change, but the electronegativity of the second group VI element is greater than that of the first group VI element, and it is easy to attract electrons around the second group VI element. As a result, the free electrons existing in the parent compound are bound to the periphery of the added second group VI element, and an expansion is generated in the wave function due to uncertainty. Moreover, the energy level (electron capture energy level) caused by the exciton bound to the impurity element, that is, the second group VI element, corresponding to the expansion of the wave function, appears in the band gap of the parent compound. Such an energy level (electron capture level) in which valence electrons are arranged and bound to an equal impurity atom is called an isoelectronic level, an isoelectronic trap, or an isoelectronic band.
[0078] When the second Group VI element is doped into the matrix 16 in this manner, a portion of the first Group VI element of the matrix compound is replaced by the second Group VI element, thereby locally changing the state of valence electrons and forming an isoelectronic level (isoelectronic band) in the band gap of the matrix compound.
[0079] Figure 4 Yes means Figure 1 The diagram is a schematic diagram showing an example of the band structure of each functional layer (HTL6, EML8, and ETL10) between the anode 4 and the cathode 12 in the light-emitting element 2 when each functional layer is in an isolated state (in other words, each functional layer is independent). Figure 5 It means that Figure 4 The schematic diagram of an example of the band structure of each functional layer in a state where each functional layer is bonded and band-shifted in a manner that the Fermi level is aligned. Figure 4 and Figure 5 As an example, the band structure of each functional layer is shown when ZnS is used as a host compound and the host material 16 of the EML 8 is doped (O doped) with a second Group VI element.
[0080] In addition, as a comparison, in addition to Figure 1 The light emitting element 2 shown in the figure is not doped with impurities in the base material 16 of the EML 8. Figure 6 In Figure 7 Indicates that Figure 1 The band structure of each functional layer in a comparative light-emitting element having the same structure as the light-emitting element 2 shown. Figure 6The diagram is a schematic diagram showing an example of the band structure of each functional layer (HTL6, EML8 and ETL10) between the anode 4 and the cathode 12 in a comparative light-emitting element including an EML8' containing a base material 16 not doped with an impurity element and QDs 14 when the functional layers are in an isolated state. Figure 7 It means that Figure 6 Schematic diagram of an example of the band structure of each functional layer in a state where each functional layer is bonded and band-shifted in a manner consistent with the Fermi level. Figure 5 as well as Figure 7 In order to compare the energy levels, the heights of the Fermi levels of the above-mentioned functional layers are made consistent.
[0081] Hereinafter, the effect obtained by the base material 16 containing the second Group VI element will be described by taking the case where O is doped as the second Group VI element as described above as an example.
[0082] As described above, O is the same Group VI element as S of the parent compound, and is a superordinate element of S in the periodic table, and therefore has a valence electron orbit equivalent to S of the parent compound and the same number of valence electrons, a greater electronegativity than S, and a smaller ion radius than S. By doping O that replaces S, an isoelectronic trap energy level is generated to locally change the valence state.
[0083] The electron trap energy levels are formed in the band gap of the parent compound of EML 8 near the lower end of the conduction band (CBM), and have a state density of at least about the doped O concentration. Figure 4 and Figure 5 As shown in FIG. 1 , when the isoelectronic trap energy level ET is formed, it has the same effect of equivalently narrowing the band gap of EML8 and effectively deepening the CBM of EML8. In addition, as the conduction band energy level is effectively deepened by O doping, the Fermi level E F The Fermi level E F It is the energy level at which the probability of the existence of an electron is 1 / 2. F In the case of an intrinsic semiconductor, it is located in the center of the band gap. Therefore, the Fermi level E F The band gap of ZnS is shifted to a position that is 1 / 2 of the energy level effectively deepened by O doping (in other words, 1 / 2 of the reduction amount of the above-mentioned band gap equivalently reduced according to the isoelectronic energy level ET). O and S have the same valence number, and the free electron density does not change due to O doping, so the base material 16 maintains the intrinsic carrier density, and the Fermi level EF of EML8 is shifted to the center of the upper end of the valence band (VBM) of EML8 and the equivalent electron energy level ET of O. In addition, since the O isoelectronic band in ZnS has a state density roughly equivalent to the added O density, the injected carriers can be transported.
[0084] On the other hand, Figure 6 as well as Figure 7 As shown, when O doping is not performed, the Fermi level difference between EML8 and HTL6 is small, and the shift of the junction between each functional layer is also small, so the hole injection barrier is high.
[0085] Therefore, if Figure 5 As shown in the figure, the shift and bending of the band generated in the junction between HTL6 and inorganic EML8 by O doping are related to Figure 7 Therefore, in the light emitting element 2, as shown in FIG. Figure 5 As shown, the hole injection barrier observed from HTL6 to the inorganic EML8 is Figure 7 Compared with the comparative light-emitting element shown in the figure, the hole injection efficiency is improved. Figure 5 and Figure 7 As shown in Figure 3, the electron injection efficiency is the same in the case of O-doped and undoped O.
[0086] In a light-emitting element using QD as a light-emitting material, generally, in the EML, the amount of electron injection is greater than the amount of hole injection. In the past, excessive electron supply and insufficient hole supply became a problem. Even if the EML8 is inorganicized by the base material 16, the point of excessive electrons will not change. Therefore, by improving the hole injection efficiency, the carrier balance of the inorganic EML8 is improved, and the external quantum efficiency (EQE) is improved.
[0087] Therefore, as described above, the light emitting element 2 includes an EML 8 and an HTL 6 disposed adjacent to the EML 8, the EML 8 includes: a matrix 16 containing at least one inorganic compound, and a plurality of QDs 14, the matrix 16 includes a matrix compound containing at least one first VI group element as the inorganic compound, and includes a second VI group element having a period number smaller than that of the first VI group element, and the total concentration of the second VI group elements in the matrix 16 is 1×10 16 Atom / cm 3 Above and 1×10 20 Atom / cm 3 When the content of the positive hole is within the following range, the carrier balance of holes and electrons can be improved, and the light-emitting element 2 having excellent light-emitting characteristics can be provided.
[0088] According to the present embodiment, as described above, the second group VI element is mixed into the base material 16 so that the total concentration of the second group VI element in the base material 16 is 1×10 16 Atom / cm 3 When the above, the second group VI element forms an isoelectronic trap level ET in the band gap of the parent compound.
[0089] The above concentration is the concentration required for the second VI group element to form the above isoelectronic trap energy level ET. If the second VI group element is mixed into the base material 16, the total concentration of the second VI group element in the base material 16 is 1×10 16 Atom / cm 3 Above and 1×10 20 Atom / cm 3 In the following range, the upper end of the valence band of HTL6 and the upper end of the valence band of EML8 are brought closer together, the hole injection barrier from HTL6 to EML8 is reduced, and the hole injection efficiency is improved.
[0090] However, when the total concentration of the second group VI elements in the matrix 16 reaches the composition level of the matrix compound constituting the matrix 16 , the valence electron orbital energy of the second group VI elements affects the interatomic bonding.
[0091] For example, as described above, when the parent compound is ZnS and the second group VI element is O, since the energy z of the valence electron orbital is O>S in both the p orbital and the s orbital, if O is the composition level of the parent compound, the band shifts in the direction of CBM shallowing. As a result, the band gap of the parent crystal is widened. In this case, since the Fermi level E F Since the displacement is shallow, the injection layer barrier to the inorganic EML8 observed from the HTL6 is expanded, and hole injection is suppressed.
[0092] Therefore, in order to make the total concentration of the second group VI elements in the matrix 16 not exceed the concentration range of the impurity level (so-called doping concentration), it is required to be lower than the concentration of the matrix compound, that is, 1×10 20 Atom / cm 3 Within the following range.
[0093] Thus, when the second Group VI element is O, the O concentration is less than the composition of the parent compound, i.e., the upper limit is 1×10 20 Atom / cm 3 (composition 0.1%). The lower limit of the concentration of O forming the above-mentioned isoelectronic trap energy level ET is 1×10 16 Atom / cm 3 Therefore, as described above, the concentration of the second group VI element in the total of the second group VI elements in the base material 16 is 1×10 16 Atom / cm 3 Above and 1×10 20 Atom / cm 3 The base material 16 is mixed in the following manner.
[0094] Furthermore, the concentration of the total of the first group VI elements in the base material 16 is preferably 10 times or more, and more preferably 10 5 times or more, greater than the concentration of the total of the second group VI elements in the base material 16 .
[0095] Since the first VI group elements are contained in the base material 16 at a composition level, the concentration of the total first VI group elements in the base material 16 is at least 1×10 21 Atom / cm 3 In addition, the base material 16 contains 1×10 21 Atom / cm 3 The above elements are the main components of the matrix 16. In other words, the matrix 16 contains 1×10 21 Atom / cm 3 The above elements are the main components of the parent compound. The main component is not limited to one element. The parent material 16 may contain two or more first group VI elements as the main component. In addition, the parent material 16 may contain a group II element as the main component. The group II element may be one of the main components or may not be the main component. In addition, the parent material 16 may also contain more than 1×10 20 Atom / cm 3 and less than 1×10 21 Atom / cm 3 The base material 16 may contain, for example, a group II element, a halogen element, or an element such as Li used for mixed crystal as an element other than the main component.
[0096] On the other hand, the total concentration of the second group VI elements in the base material 16 is at most 1×10 20 Atom / cm 3 Therefore, the concentration of the total of the first group VI elements in the base material 16 is more than 10 times greater than the concentration of the total of the second group VI elements in the base material 16. In addition, the concentration of the total of the second group VI elements in the base material 16 is an impurity concentration as described above, and considering the detection limit, the lower limit is 1×10 16 Atom / cm 3 Therefore, it is more preferable that the concentration of the total of the first group VI elements in the base material 16 is 10 greater than the concentration of the total of the second group VI elements in the base material 16. 5 times or more.
[0097] In addition, as described above, O is doped in the matrix 16 as an impurity, and by analyzing the element concentration using an electron beam microanalyzer (EPMA), it can be determined that O is introduced into the crystal of the matrix compound based on the chemical shift of O. Thus, it can be determined by EPMA that the matrix 16 is doped with a second Group VI element as an impurity.
[0098] In addition, the concentration of the total of the second group VI elements in the base material 16 can be measured by secondary ion mass spectrometry (SIMS). The above concentration can be measured by Auger electron spectroscopy (AES). The lower limit of the detection accuracy is SIMS (ppm) < AES (%), SIMS is 10,000 times that of AES, and the detection accuracy is high. In addition, the lower limit of the spatial resolution is AES (30nm) < SIMS (200nm), SIMS is 6.7 times that of AES, and the spatial resolution is rough, but even SIMS can be analyzed at a scale sufficiently smaller than one pixel. Therefore, AES can also be used to measure the above concentration, but it is more preferable to use SIMS with high detection accuracy.
[0099] In the present embodiment, since the organic ligand is removed by inorganicization, it can be determined that the second group VI element detected by SIMS, EPMA, etc. is not derived from an organic substance but is added to the base material 16 .
[0100] Figure 8 It is a graph showing the JV characteristics of the light emitting element 2 of this embodiment in which the matrix 16 having ZnS as the matrix compound is doped with O and the JV characteristics of the light emitting element for comparison in which the matrix 16 having ZnS as the matrix compound is not doped with O.
[0101] exist Figure 8 In FIG. 1 , the solid line represents the voltage applied to the light emitting element 2 as a JV characteristic and the voltage Figure 1 The relationship between the current flowing through the light emitting element 2 via the junction of HTL6, EML8 and ETL10 is shown in I. The dotted line shows the relationship between the voltage applied to the light emitting element for comparison and the current flowing through the light emitting element for comparison via the junction of HTL6, EML8 and ETL10 in the light emitting element for comparison as a JV characteristic.
[0102] from Figure 8 It is found that by doping the base material 16 with O, the rising voltage of the current of the light emitting element 2 is reduced by about 1 V compared with the rising voltage of the current of the comparative light emitting element, and changes in a direction in which the slope becomes steeper.
[0103] Generally speaking, the current flowing through the light emitting element shows a slope that is steeper as the injected carriers recombine for light emission more efficiently. As described above, the current I flowing through the light emitting element 2 via the junction of HTL6, EML8 and ETL10 contributes to the light emission recombination of carriers.
[0104] Therefore, from Figure 8 It is inferred from the results shown that carriers are efficiently injected into the inorganic EML 8 by doping the base material 16 with O, and the light emission recombination efficiency of the injected carriers is improved.
[0105] Fig. 9 and Fig.10 It is a graph showing the luminescence characteristics of the above-mentioned light-emitting element 2 of this embodiment in which O-doping is performed on the matrix 16 with ZnS as the matrix compound, and the luminescence characteristics of the above-mentioned comparative light-emitting element in which O-doping is performed on the matrix 16 with ZnS as the matrix compound.
[0106] exist Fig. 9 In FIG. 1 , the solid line represents the relationship between the current density applied to the light-emitting element 2 and the external quantum efficiency (EQE) as the luminescence characteristic, and the dotted line represents the relationship between the current density applied to the light-emitting element for comparison and the EQE as the luminescence characteristic. Fig.10 In FIG. 1 , the solid line represents the relationship between the voltage applied to the light emitting element 2 and EQE as the light emitting characteristic, and the dotted line represents the relationship between the voltage applied to the light emitting element for comparison and EQE as the light emitting characteristic.
[0107] EQE relative to current density, such as Fig. 9 As shown, the maximum value (peak EQE) of the EQE of the light-emitting element for comparison is about 5%, while the peak EQE of the light-emitting element 2 is about 12%. By doping the base material 16 with O, the EQE is greatly improved. Figure 8 The JV characteristics shown in the figure are consistent with the prediction. In addition, the current density indicating the peak EQE is 1 mA / cm in the above-mentioned comparative light-emitting element. 2 Next, in contrast, the light emitting element 2 shifts to 10 mA / cm 2 This indicates that carriers can be injected to a level that is commensurate with the light-emitting recombination rate of QDs 14 contained in the inorganic EML 8. This result indicates that the current flowing through the light-emitting element 2 is injected into the EML 8 without waste, contributing to light emission.
[0108] In addition, if Fig.10 As shown, the voltage at which the peak EQE of the light-emitting element 2 is shifted to the lower voltage side by about 2 V compared with the light-emitting element for comparison, indicating that the injection loss of carriers is significantly reduced.
[0109] In addition, the base material 16 may further contain at least one halogen element. Figure 2 As shown, the base material 16 may contain halide ions 16H, and the halide ions 16H include at least one of fluoride ions, chloride ions, bromide ions, and iodide ions.
[0110] The halogen element is stabilized by bonding with the unpaired electrons of the parent compound, and thus can inactivate the defects of the parent material 16. In addition, here, "inactivating the defects of the parent material 16" means that the defects no longer function as non-luminescent centers or carrier traps by using the unpaired electrons to bond with the halogen element. Figure 2 As shown, since the halide ions 16H exist near the surface of QD 14, the dispersibility of QD 14 is improved. Therefore, the base material 16 preferably contains a halogen element. In addition, the thickness of the shell 14S can be approximately within the range of the surface of QD 14.
[0111] The matrix 16 may contain 1 atomic % or more of halogen elements. The total concentration of the halogen elements in the matrix 16 is preferably 1×10 16 Atom / cm 3 In addition, the total concentration of the halogen elements in the base material 16 is preferably 1×10 19 Atom / cm 3 the following.
[0112] The halogen elements may be contained in the base material 16 to such an extent that the defects of the base material 16 are filled. It is sufficient that the total concentration of the halogen elements in the base material 16 is much lower than the concentration of the composition of the base material 16. If the total concentration of the halogen elements in the base material 16 reaches the level of the composition of the base material 16, the properties of the base material 16 may change. In addition, if the halogen elements that are not introduced into the composition of the base material 16 exist at a high density, the quality of the base material 16 is likely to be significantly reduced.
[0113] Therefore, considering that (i) the total concentration of the halogen elements in the matrix 16 needs to be set lower than the composition level of the matrix 16 as described above, and (ii) the surface defect density of the heteroepitaxially grown GaN / sapphire with high defect density is 1×10 9 / cm 2 (iii) the temperature of synthesizing the matrix 16 is lower than the general semiconductor growth temperature; (iv) a II-VI compound that is prone to IV defects is used in the matrix compound; (v) the defect surface density in the matrix 16 is estimated to be at least 1×10 10 / cm 2 As a value that makes the defects fully inactive and detectable, the concentration of the total halogen elements in the base material 16 is preferably 1×10 16 Atom / cm 3 Above and 1×10 19 Atom / cm 3 the following.
[0114] The concentration of halide ions 16H near each QD 14 in the EML 8 is preferably higher than that of halide ions 16H in the surrounding area. For example, the area around a certain QD 14 within 1 nm from the outermost surface of the QD 14 may be defined as the vicinity of the QD 14.
[0115] So, for example Figure 2 As shown, in the periphery of QD14, the average value of the total concentration of halogen atoms within a distance DA of 1 nm from the outermost surface of the QD14, i.e., the outer surface of the shell 14S, may be higher than the average value of the total concentration of halogen atoms at other positions. In this case, the average value of the total concentration of halogen atoms within the distance DA of 1 nm may be higher than the average value of the total concentration of halogen atoms at other positions by 10% or more, or by 50% or more, or by 100% or more. Such a concentration distribution can be confirmed, for example, by element mapping based on cross-sectional TEM-EDX (transmission electron microscopy-energy dispersive X-ray spectroscopy).
[0116] In addition, here, "other positions" can also be said to be positions where there is no QD14 within 1 nm. EML8 contains multiple QD14. Therefore, the above value can also be a value when the average value of the concentration of the total amount of halogen atoms within 1 nm around each QD14 in EML8 is compared with the average value of the concentration of the total amount of halogen atoms in the part where any QD14 in EML8 is more than 1 nm away.
[0117] That is, it is preferred that the average value of the concentration of the total of halogen elements in a region within 1 nm from the outermost surfaces of each of the multiple QDs 14 in the matrix 16 is higher than the average value of the concentration of the total of the halogen elements in a region more than 1 nm away from the outermost surfaces of each of the multiple QDs 14 in the matrix 16, and may be, for example, 10% or more, 50% or more, or 100% or more.
[0118] This can further improve the dispersibility of the QDs 14 and form the EML 8 with a more uniform thickness.
[0119] The base material 16 may contain halide ions by forming the EML 8 using a QD dispersion liquid containing a halogen element and the QDs 14 .
[0120] (Method for Manufacturing Light Emitting Element 2) Below, refer to Fig.11 , a method for manufacturing the light emitting element 2 of this embodiment is described. Fig.11 This is a flowchart showing an example of a method for manufacturing the light emitting element 2 according to the present embodiment.
[0121] like Fig.11As shown, in the method for manufacturing the light emitting element 2 of this embodiment, first, in the Fig.14 An anode 4 is formed on the substrate 3 as a support shown (step S1, anode forming process). Then, HTL 6 is formed (step S2, HTL forming process). In addition, a QD dispersion liquid (adjusting liquid) is manufactured in parallel (step S11, QD dispersion liquid manufacturing process). Then, EML 8 is formed using the above-mentioned QD dispersion liquid (step S3, EML forming process). Then, ETL 10 is formed (step S4, ETL forming process). Then, a cathode 12 is formed (step S5, cathode forming process). Thus, the above-mentioned light-emitting element 2 is manufactured.
[0122] In forming the anode 4 in step S1 and forming the cathode 12 in step S5 , for example, a vapor deposition method, a sputtering method, or the like is used.
[0123] In the formation of the HTL 6 in step S2 and the formation of the ETL 10 in step S4 , for example, a vacuum deposition method, a sputtering method, a coating method using a colloidal solution, a sol-gel method, or the like is used.
[0124] Here, before explaining step S3 , step S11 will be explained in more detail.
[0125] (Step S11) The QD dispersion preparation step of step S11 includes a ligand replacement step (step S21 ) of replacing the ligand coordinated to the QD 14 .
[0126] In the QDs obtained synthetically or commercially, in most cases, an organic ligand is usually coordinated as a ligand. Commercially available QDs are generally provided in the state of a QD dispersion containing an organic ligand. The organic ligand is used as a dispersant to improve the dispersibility of the QD in the QD dispersion, and is also used as a dispersant to improve the surface stability and storage stability of the QD. In addition, the synthesis of QD uses, for example, a wet method to control the particle size of the QD by making the organic ligand coordinated to the surface of the QD. Therefore, the QD dispersion synthesized by the wet method contains the organic ligand used in the synthesis of the QD. Therefore, in the present embodiment, in order to invalidate EML8, a ligand replacement process is implemented to replace the ligand coordinated to QD14.
[0127] In the present embodiment, as the QD dispersion liquid, for example, a QD dispersion liquid containing QDs coordinated with halide ions is used. Therefore, in the ligand replacement step, the organic ligands are replaced with halide ions, so that the halide ions are coordinated to the QDs 14 .
[0128] Below, refer to Fig.12 , a method for replacing the organic ligand coordinated to QD14 with the halide ion 16H is described.
[0129] Fig.12 It is used to illustrate Fig.11 Schematic cross-sectional view of the ligand replacement process (step S21) shown in FIG. Fig.12 As shown, in the above-mentioned ligand replacement process, first, a first solution 20 in which halide ions 16H are dissolved and a second solution 22 in which QD14 is dispersed are injected into a container 18 (step S21a), and the QD14 is coordinated with a carbon chain CC as an organic ligand. The first solution 20 contains a first solvent 24 in which halide ions 16H are soluble, and the second solution 22 contains a second solvent 26 in which carbon chain CC is soluble. For example, the polarity of the second solvent 26 is different from the polarity of the first solvent 24, and the specific gravity is lighter than that of the first solvent 24. In order to more clearly distinguish the boundary between the first solution 20 and the second solution 22, a separation liquid 28 having a specific gravity and polarity between the first solvent 24 and the second solvent 26 can also be injected into the container 18.
[0130] The first solvent 24 may contain at least one organic solvent selected from, for example, dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N-methylformamide (NMF), formamide, N,N'-dimethylpropylene urea, dimethylacetamide, N-methylpyrrolidone, γ-butyrolactone, propylene carbonate, acetonitrile, 2-methoxyethanol, methyl acetate, ethyl acetate, ethyl formate, methyl formate, tetrahydrofuran, diethyl ether, tetrahydrothiophene and diethyl sulfide. At this time, the first solvent 24 makes the QD14 coordinated by the halide ion 16H well dispersed together with the precursor of the base material 16. In addition, the first solvent 24 can also be a polar solvent with a greater polarity than the second solvent 26. The first solvent 24 can be prepared by, for example, dispersing zinc chloride, sodium chloride, hydrochloric acid, etc. in NMF, DMF, DMSO, etc. The second solvent 26 is preferably, for example, toluene, hexane, octane, octadecene, etc. The second solvent 26 is preferably a non-polar solvent that is not miscible with the first solvent 24.
[0131] The carbon chain CC may also be a carbon chain commonly used as a ligand of QD. The second solvent 26 is a solvent in which the carbon chain CC is soluble, so the QD14 coordinated by the carbon chain CC is easily dispersed in the second solution 22. In addition, an excess of halide ions 16H exceeding the amount of halide ions 16H that can coordinate with QD14 is dissolved in the first solution 20. The concentration of halide ions 16H in the first solvent 24 is preferably 0.01 mol / L or more, and more preferably 0.1 mol / L or more.
[0132] Next, the first solution 20 and the second solution 22 are stirred by vibrating the container 18 containing the first solution 20 and the second solution 22 at high speed using a stirrer (step S21b). In order to improve the stirring efficiency, a stirrer may also be added to the container 18. In other words, the process of stirring the first solution 20 and the second solution 22 is a process of treating QD14 with halide ions 16H, in particular, a process of generating QD14 coordinated with halide ions 16H.
[0133] Here, as described above, the first solution 20 contains an excess of halide ions 16H. Generally speaking, when the solution in which QDs are dispersed contains two or more ligands, the ligands coordinated to the QDs are in equilibrium between the ligands in the solution. Therefore, when the first solution 20 and the second solution 22 are stirred, at least a portion of the ligands coordinated to the QD14 are replaced by the carbon chain CC with the halide ions 16H.
[0134] For example, in step S21b, the solution in the container 18 is stirred for at least 1 minute. In addition, the stirring of the solution in the container 18 may be performed for 1 hour at a vibration frequency of 10 times per minute while the temperature of the solution in the container 18 is set to 25°C. Under this condition, it can be said that the possibility that the ligand of the QD 14 coordinated in the container 18 is replaced by the halide ion 16H is sufficiently high. In order to prevent water or oxygen in the atmosphere from mixing with the solution in the container 18, it is more preferable to stir the solution in the container 18 under an atmosphere of nitrogen or argon.
[0135] Therefore, by the above stirring, Fig.12 As shown in step S21b, a third solution 30 in which QD14 coordinated with halide ions 16H is dispersed in the first solvent 24 and a fourth solution 32 in which the carbon chain CC is dissolved in the second solvent 26 is obtained in the container 18. As described above, QD14 coordinated with halide ions 16H is obtained in the third solution 30. In addition, the above stirring can also be completed at the stage of irradiating ultraviolet rays or the like to the liquid in the container 18 and confirming that the luminescent liquid layer moves from the upper part of the container 18 to the lower part.
[0136] Next, a QD dispersing step (step S22) is performed to disperse the QD 14 coordinated with the halide ions 16H and the precursor of the matrix 16 in a solvent. Thus, in step S3, a QD dispersion liquid is manufactured, which contains the QD 14 coordinated with the halide ions 16H, the precursor of the matrix 16, and the solvent used in the formation of the EML 8.
[0137] Fig.13 This is a cross-sectional view showing a schematic structure of the QD dispersion liquid 38 produced in step S22 and used for forming the light-emitting element 2 of this embodiment.
[0138] In step S22, for example, after step S21, only the third solution 30 is extracted from the container 18 using a pipette or the like. Then, the extracted third solution 30 and the precursor 36 of the base material 16, for example, a precursor solution dispersed in the first solvent 24 are mixed. Fig.13 The mixture is mixed in the container 34 shown. Fig.13 As shown, QD 14 coordinated with halide ion 16H and precursor 36 are dispersed in, for example, first solvent 24 to produce QD dispersion 38 (prepared solution) containing the QD 14, precursor 36 and first solvent 24.
[0139] In addition, the precursor solution may be injected into the container 18 before the third solution 30 is injected, or the precursor solution may be injected into the container 18 after or at the same time as the third solution 30 is injected. The order of adding (injecting) the third solution 30 and the precursor solution is not particularly limited.
[0140] The precursor 36 contains a first group VI element. When the first group VI element is S and the parent compound is a metal sulfide such as ZnS as described above, the precursor 36 may include at least one metal source selected from metals containing a group II element as a metal element, such as metal acetates, metal nitrates, and metal halides.
[0141] Furthermore, in this case, as a first Group VI element source containing a first Group VI element, the precursor 36 may contain at least one sulfur source selected from the group consisting of sulfur as a first Group VI element, such as thiourea, N-methylthiourea, 1,3-dimethylthiourea, N,N'-dimethylthiourea, tetramethylthiourea, and thioacetamide.
[0142] In addition, the precursor 36 may also include a metal complex in which thiourea, N-methylthiourea, 1,3-dimethylthiourea, N,N′-dimethylthiourea, tetramethylthiourea or thioacetamide is coordinated to a metal element (eg, a metal atom).
[0143] The second Group VI element may be contained in the precursor 36, in the first solvent 24 in which the precursor 36 is dispersed, or added after the third solution 30 is mixed with the precursor solution. The method of mixing (doping) the second Group VI element into the matrix 16 is not particularly limited.
[0144] When the matrix 16 contains O as the second group VI element, as a method for mixing O into the matrix 16, for example, a method of adjusting the pH of the QD dispersion 38 so that the pH of the QD dispersion 38 becomes slightly acidic, for example, about pH 6.5. In order to adjust the pH of the QD dispersion 38, an acid may be added. By adding a trace amount of acid to slightly lower the pH, the OH - A slight increase in the concentration can cause O to be mixed into the base material 16 to a certain extent.
[0145] The required amount of the acid used for pH adjustment can be determined by the following formula (1). pH removal formula (1) Z=(N×n×Q×10 5 ) / (60×W×D)…(1), n(H + The common logarithm of the concentration) can be used.
[0146] In formula (1), Z represents the required amount of acid (mL). N represents the gram equivalent of the acid (g). n represents the target H + concentration (mol / L). Q represents the total amount of solvent (m 3 ). For example, when the first solvent 24 is used as the solvent as described above, Q represents the total amount of the first solvent 24. W represents the concentration of the acid (wt%). D represents the specific gravity of the acid.
[0147] As the acid, for example, hydrochloric acid (HCl), sulfuric acid (H2SO4), phosphoric acid (H3PO4), etc. can be used. Among these acids, HCl that does not contain P, S, etc. is preferably used. HCl is composed only of the elements contained in the precursor 36 for inorganicization and the first solvent 24, so that foreign elements are not mixed into the base material 16.
[0148] By adding the acid in this way, the pH of the first solvent 24 as a solvent changes, and the pH of the QD dispersion 38 changes. If the pH of the QD dispersion 38 changes, the reaction of the precursor 36 also changes. Therefore, in the case of adjusting the pH of the QD dispersion 38 by lowering the pH of the QD dispersion 38 with an acid, for example, if the reaction temperature is changed according to the pH or the reaction temperature is not changed, it is preferable to extend the reaction time. In this way, the layer thickness of the inorganic EML 8 can be kept constant.
[0149] In the case where the base material 16 contains a group VI element other than O as the second group VI element, in order to mix the second group VI element other than O into the base material 16, for example, a precursor 36 containing a source of the second group VI element at the above-mentioned impurity concentration may be used. In addition, as a compound containing the second group VI element, a compound of the same group II element as the source of the group II element contained in the precursor 36 may be dispersed in the first solvent 24 together with the precursor 36 to prepare a QD dispersion 38, wherein the concentration of the second group VI element in the base material 16 is 1×10 16 Atom / cm 3 Above and 1×10 20 Atom / cm 3 The following in-scope approach includes a plurality of QDs 14 , a precursor 36 including a first Group VI element, a compound including a second Group VI element, and a first solvent 24 .
[0150] Next, step S3 will be described in more detail.
[0151] (Step S3) Fig.14 It is a process cross-sectional view showing an example of a method for forming the EML 8.
[0152] like Fig.14 As shown in S2 in FIG. 1 , at the end of step S2 , the substrate 3 , the anode 4 and the HTL 6 are formed.
[0153] In step S3, first, the QD dispersion liquid 38 produced in step S11 is applied on the HTL 6. Thus, a coating layer 8A containing the QD dispersion liquid 38 is formed as a coating film on the HTL 6 (step S31, QD dispersion liquid application step).
[0154] In addition, as a method for forming the coating film, for example, any method such as a bar coating method, a spin coating method, an ink jet method, etc. can be appropriately selected.
[0155] Next, the coating layer 8A is fired (heated) or the like to remove the first solvent 24 contained in the coating layer 8A, and the coating layer 8A is dried (step S32 , solvent removal step).
[0156] As an example, in step S32, for example, after step S31, the coating layer 8A is dried by heating the laminate from the substrate 3 to the coating layer 8A at a temperature of 80°C to 500°C for more than 1 minute. As the coating layer 8A is dried, the precursor 36 is denatured (crystallized). Thus, a matrix compound containing at least one first group VI element as a main component and a matrix 16 containing at least one second group VI element at the above-mentioned impurity level concentration (so-called doping concentration) relative to the matrix 16 is formed. Thus, an EML 8 including a matrix 16 containing a first group VI element and a second group VI element and QDs 14 is formed on the HTL 6.
[0157] As described above, the concentration of the second group VI element in the EML8 that has been inorganicized by such a step can be quantified by, for example, SIMS. For example, the precursor 36 uses zinc acetate (ZnC4H6O4) as a metal source, thiourea (CH4N2S) as a sulfur source, dimethyl sulfoxide as a first solvent 24, and HCl as an acid, and the pH of the QD dispersion 38 is adjusted to, for example, pH 6.5 to form an EML8 containing ZnS as a parent compound and O as a second group VI element. The concentration of O contained in the EML8 measured by SIMS is 1×10 16 Atom / cm 3 In addition, the chemical shift of O can be evaluated by EPMA to determine whether O as a second group VI element is doped as an impurity. In addition, since the organic ligand is removed by inorganicization, it can be determined that the O detected in SIMS and EPMA is not derived from organic matter but is added to the base material 16.
[0158] The O concentration is at an impurity level (so-called doping concentration) relative to the matrix 16 and does not reach the composition of the matrix compound. The O concentration is higher than the concentration required for O to form the isoelectronic trap level ET.
[0159] Therefore, in this case, O forms an isoelectronic trap level ET in the band gap of ZnS, which is the parent compound. As a result, as described above, the CBM of HTL6 and the CBM of EML8 are close to each other, the hole injection barrier from HTL6 to EML8 is reduced, and the hole injection efficiency is improved. As a result, the carrier balance between holes and electrons is improved, as described above. Figure 8 to Figure 10 As shown, a light-emitting element 2 having excellent light-emitting characteristics can be obtained.
[0160] In addition, as described above, when the halide ion 16H is coordinated with the shell 14S of QD14, the dispersibility of QD14 in the polar solvent is high, and it is difficult to produce precipitation of QD14. In addition, by coordinating the halide ion 16H with the shell 14S of QD14, the aggregation of QD14 caused by the reaction of the precursor 36 on the surface of QD14 can be suppressed, and the dispersibility of QD14 can be maintained for a long time.
[0161] In addition, when the first solvent 24 of the QD dispersion 38 is dried from step S31 to step S32, the concentration of QD 14 in the QD dispersion 38 becomes high. However, as described above, if the halide ion 16H is coordinated with the shell 14S of the QD 14, it is possible to suppress the precipitation of QD 14 before the precursor 36 is deposited on the HTL 6. Therefore, by the halide ion 16H being coordinated with the shell 14S of the QD 14, it is possible to form a smoother EML 8 in which the QD 14 is more uniformly dispersed.
[0162] In addition, as described above, in order to form the EML 8 in the above step S32, the laminate from the substrate 3 to the coating layer 8A is heated to, for example, 80° C. to 500° C. Therefore, all layers from the anode 4 to the coating layer 8A are preferably formed of layers containing inorganic materials. In addition, it is more preferred that all layers from the anode 4 to the cathode 12 are formed of layers containing inorganic materials.
[0163] (Variation Example) exist Figure 1 In the embodiment, the anode 4 is a lower electrode, the cathode 12 is an upper electrode, and the EML 8 is provided on the HTL 6. However, the present disclosure is not limited thereto.
[0164] The light emitting element 2 may also have a cathode 12 as a lower electrode, an anode 4 as an upper electrode, and an HTL 6 disposed on an EML 8. Therefore, the light emitting element 2 may also have a structure in which, for example, the cathode 12, ETL 10, EML 8, HTL 6, and anode 4 are disposed in order from the lower layer side (for example, the support body side of the substrate 3, etc., which is not shown).
[0165] In this case, the stacking order of the light emitting element 2 is Figure 1 The light-emitting element 2 shown is the opposite. Therefore, when manufacturing such a light-emitting element 2, first, a cathode 12 is formed on a substrate 3 serving as a support (step S5, cathode forming process). Then, ETL 10 is formed (step S4, ETL forming process). In addition, a QD dispersion (adjusting liquid) is manufactured in parallel (step S11, QD dispersion manufacturing process). Then, EML 8 is formed using the above-mentioned QD dispersion (step S3, EML forming process). Next, HTL 6 is formed (step S2, HTL forming process). Next, an anode 4 is formed (step S1, anode forming process). The above-mentioned light-emitting element 2 is thus manufactured.
[0166] In this case, the light emitting element 2 may include a functional layer (not shown) other than the HTL 6 , the EML 8 , and the ETL 10 between the anode 4 and the cathode 12 .
[0167] [Second embodiment] (Schematic Structure of Light Emitting Element 2) Fig.15 It is a cross-sectional view showing a schematic structure of the light emitting element 2 according to the present embodiment.
[0168] like Fig.15 As shown, the light emitting element 2 includes an ETL 10 provided adjacent to the EML 8 on the side opposite to the HTL 6 via the EML 8 .
[0169] In the light-emitting element 2 of the present embodiment, the total concentration of the second group VI elements in the base material 16 closer to the HTL6 side than the center in the thickness direction of the EML 8 is greater than the total concentration of the second group VI elements in the base material 16 closer to the electron transport layer side than the center in the thickness direction of the EML 8. Therefore, in the EML 8 of the light-emitting element 2 of the present embodiment, the base material 16 has a first portion P1 having a relatively large total concentration of the second group VI elements and a second portion P2 having a relatively small total concentration of the second group VI elements.
[0170] For example, Fig.15 As shown, the EML 8 may have a structure in which a first EML 8 a having a relatively high total concentration of the second group VI elements in the base material 16 and a second EML 8 b having a relatively low total concentration of the second group VI elements in the base material 16 are stacked.
[0171] For example, the EML 8 may include: a first EML 8a adjacent to the HTL 6; and a second EML 8b disposed between the first EML 8a and the ETL 10 and adjacent to the first EML 8a and the ETL 10, respectively. In this case, the base material 16 of the first EML 8a is the first portion P1, and the base material 16 of the second EML 8b is the second portion P2. However, this is not limited to this, and for example, as described later, Fig.18 As shown, an intermediate layer is provided between the first EML 8a and the second EML 8b.
[0172] Fig.15 The light-emitting element 2 shown, as an example, has an anode 4, an HTL 6, an EML 8 consisting of a first EML 8a and a second EML 8b arranged on the first EML 8a, an ETL 10, and a cathode 12, which are arranged in sequence from the lower layer side (for example, the supporting body side of the above-mentioned substrate 3, etc. not shown).
[0173] The first EML8a and the second EML8b have the same layer thickness as each other, and as described above, have the same composition except that the concentration of the sum of the second group VI elements in the base material 16 is different. The total layer thickness of the first EML8a and the second EML8b can be greater than the layer thickness of the EML8 of the first embodiment, but is preferably the same as the layer thickness of the EML8 of the first embodiment. The layer thickness of EML8 is designed to be most suitable for light extraction efficiency. Therefore, even when EML8 is divided into the first EML8a and the second EML8b, the highest luminous efficiency can be obtained by not changing the overall layer thickness of EML8 according to the most suitable layer thickness.
[0174] The total concentration of the second group VI element in the base material 16 on the side closer to the HTL 6 than the center in the thickness direction of the EML 8 may be within 1×10 19 Atom / cm 3 Above and 1×10 20 Atom / cm 3 Therefore, the total concentration of the second group VI element in the first portion P1 in the first EML 8a may be within a range of 1×10 19 Atom / cm 3 Above and 1×10 20 Atom / cm 3 Within the following range.
[0175] In addition, the total concentration of the second group VI element in the base material 16 closer to the ETL 10 than the center in the thickness direction of the EML 8 may be within 1×10 16 Atom / cm 3 Above and 1×10 18 Atom / cm 3 Therefore, the total concentration of the second group VI element in the second portion P2 in the second EML 8b may be within a range of 1×10 19 Atom / cm 3 Above and 1×10 20 Atom / cm 3 However, as described above, the premise is that the condition of (the total concentration of the second group VI element in the first part P1)>(the total concentration of the second group VI element in the second part P2 in the second EML 8b) is satisfied.
[0176] However, the present embodiment is not limited thereto. The second VI group element may also be mixed only in the base material 16 closer to the HTL6 side than the center in the thickness direction of the EML 8. Therefore, the second VI group element may be mixed only in the second EML 8b of the first EML 8a and the second EML 8b, or the second VI group element may be mixed only in the first part P1 of the first part P1 and the second part P2.
[0177] In addition, in this case, the second Group VI element may also be mixed and exist in a thickness of 1 / 2 of the thickness of EML 8.
[0178] In either case, as described above, by making the concentration of the second Group VI element relatively high on the side closer to the HTL 6 than the center in the thickness direction of the EML 8 , the hole injection efficiency can be improved, thereby further improving the EQE.
[0179] In addition, as described above, when the concentration of the sum of the second VI group elements near the HTL6 side is relatively large, as time passes, the second VI group elements diffuse from EML8 to HTL6. For example, when the second VI group element is O as described above, as time passes, O diffuses from EML8 to HTL6, suppressing the oxygen deficiency of HTL6. In the case where the aforementioned HIL is provided between HTL6 and the anode 4, as time passes, O diffused from EML8 to HTL6 diffuses to HIL, suppressing the oxygen deficiency of HTL6 and HIL. In particular, the HIL composed of an inorganic material becomes a source of free electrons due to oxygen deficiency, so if oxygen deficiency is suppressed, it is possible to suppress the obstruction of hole transport due to oxygen deficiency. As a result, a light-emitting element 2 with high reliability can be obtained.
[0180] Fig.16 It means in Fig.15 In the light-emitting element 2 shown, a second Group VI element is mixed only in the first part P1 of the first EML8a, and a schematic diagram of an example of the band structure of each functional layer when the functional layers (HTL6, first EML8a, second EML8b, and ETL10) between the anode 4 and the cathode 12 are in an isolated state. Fig.17 It means that Fig.16 Schematic diagram of an example of the band structure of each functional layer in a state where each functional layer is bonded and band-shifted in a manner consistent with the Fermi level. Fig.15 and Fig.16 , as an example, the band structures of the functional layers are shown when O, which is a second Group VI element, is doped (O doping) only in the first portion P1 of the base material 16 of the EML 8 having ZnS as a base compound.
[0181] like Fig.15 and Fig.16As shown, regarding the light-emitting element 2 of this embodiment, the concentration of O in the first EML 8a is higher than the concentration of O in the second EML 8b, and the Fermi level EF of the first EML 8a close to the HTL 6 side is shifted to the center of the VBM of the EML 8 and the isoelectronic energy level ET of O. Therefore, the hole injection barrier to the first EML 8a observed from the HTL 6 is lowered, and the hole injection efficiency is improved. Therefore, as described above, the EQE can be further improved.
[0182] (Method for Manufacturing Light Emitting Element 2) In this embodiment, QD 14 is applied twice in step S3. Specifically, in step S11, two types of QD dispersions 38 having different contents of the second group VI element are prepared as QD dispersions 38, and in step S3, steps S31 and S32 are repeated twice using the respective QD dispersions 38.
[0183] When the second Group VI element is O, and O is doped only in the first portion P1 of the first EML 8 a , it is sufficient to add an acid only to the QD dispersion liquid 38 for forming the first EML 8 a .
[0184] When the second group VI element is O, and the first part P1 of the first EML 8a and the second part P2 of the second EML 8b respectively contain O as the second group VI element, the concentration of the acid added to the QD dispersion liquid 38 used to form the second EML 8b is lower than the concentration of the acid added to the QD dispersion liquid 38 used to form the first EML 8a. Alternatively, the amount of the acid added to the QD dispersion liquid 38 used to form the second EML 8b may be reduced to be less than the amount of the acid added to the QD dispersion liquid 38 used to form the first EML 8a.
[0185] (Variation Example) The concentration of the sum of the second group VI elements in the base material 16 decreases as it approaches the ETL 10 in the thickness direction of the EML 8. However, in this case, the concentration of the sum of the second group VI elements in the base material 16 does not necessarily decrease linearly as it approaches the ETL 10, but may decrease in stages. The concentration of the sum of the second group VI elements in the base material 16 may change continuously or in stages.
[0186] In the present disclosure, “the concentration of the total of the second Group VI elements in the base material 16 decreases as it is closer to ETL10 in the thickness direction of EML8” means both a case where the concentration of the total of the second Group VI elements in the base material 16 decreases linearly as it is closer to ETL10 in the thickness direction of EML8 and a case where the concentration of the total of the second Group VI elements in the base material 16 decreases stepwise as it is closer to ETL10.
[0187] In either case, when the EML 8 is divided into a side closer to the HTL 6 than the center in the thickness direction of the EML 8 and a side farther from the EML 6 (i.e., the ETL 10 side), the total concentration of the second group VI element in the base material 16 on the side closer to the HTL 6 than the center in the thickness direction of the EML 8 can also be within 1×10 19 Atom / cm 3 Above and 1×10 20 Atom / cm 3 In addition, the total concentration of the second group VI element in the base material 16 closer to the ETL 10 than the center in the thickness direction of the EML 8 may be within the range of 1×10 16 Atom / cm 3 Above and 1×10 18 Atom / cm 3 Within the following range.
[0188] Fig.18 It is a cross-sectional view showing an example of a schematic configuration of a light emitting element 2 according to this modification.
[0189] Fig.18 In the description, as an example, the EML 8 has a structure in which a first EML 8 a ′, a second EML 8 b ′, and a third EML 8 c ′ are sequentially stacked from the HTL 6 side, and the total concentration of the second group VI element in the base material 16 decreases stepwise.
[0190] Fig.18 The EML 8 of the light-emitting element 2 shown has a first portion P11, a second portion P12, and a third portion P13, each of which has a different concentration of the total of the second VI elements in the base material 16. The concentration of the total of the second VI elements in the second portion P12 is lower than the concentration of the total of the second VI elements in the first portion P11, and the concentration of the total of the second VI elements in the third portion P13 is lower than the concentration of the total of the second VI elements in the second portion P12. In this case, the base material 16 of the first EML 8a' is the first portion P11, the base material 16 of the second EML 8b' is the second portion P12, and the base material 16 of the third EML 8c' is the third portion P13.
[0191] The first EML8a', the second EML8b', and the third EML8c' have the same layer thickness as each other, and as described above, have the same configuration except that the concentration of the total of the second group VI elements in the base material 16 is different. The total layer thickness of the first EML8a', the second EML8b', and the third EML8c' may be greater than the layer thickness of the EML8 of the first embodiment, but is preferably the same as the layer thickness of the EML8 of the first embodiment. In this case, the highest luminous efficiency can be obtained.
[0192] In this case, as described above, since the concentration of the second Group VI element is relatively high on the side closer to the HTL 6 than on the side closer to the ETL 10 , the hole injection efficiency can be improved, and the EQE can be further improved.
[0193] In this case, since the total concentration of the second group VI element near the HTL6 side is relatively large, for example, when the second group VI element is O as described above, O diffuses from the EML8 to the HTL6 over time, thereby suppressing oxygen deficiency in the HTL6. Therefore, a light-emitting element 2 with high reliability can be obtained.
[0194] (Method for Manufacturing Light Emitting Element 2) In the formation Fig.18 In the case of the light-emitting element 2 shown, in step S3, QD 14 is applied three times. Specifically, in step S11, three QD dispersions 38 with different content ratios of the second group VI element are manufactured as QD dispersions 38, and in step S3, steps S31 and S32 are repeated three times using the respective QD dispersions 38. In addition, in this case, in the third EML 8c' closest to the ETL 10, it does not matter if the base material 16 does not contain the second group VI element.
[0195] In order to gradually reduce the concentration of the total of the second VI elements in the base material 16 as the portion closer to the ETL 10 in the thickness direction of the EML 8 is reduced, for example, when the second VI element is O, the concentration of the acid added to the QD dispersion 38 used to form the EML near the ETL 10 side may be gradually reduced compared to the concentration of the acid added to the QD dispersion 38 used to form the EML near the HTL 6 side. Alternatively, the amount of the acid added to the QD dispersion 38 used to form the EML near the ETL 10 side may be gradually reduced compared to the amount of the acid added to the QD dispersion 38 used to form the EML near the HTL 6 side.
[0196] Alternatively, in step S31, the QD dispersion 38 may be continuously supplied and coated on the HTL 6. Alternatively, the acid having different concentrations may be dripped (supplied) in multiple times, or the acid dripping amount may be changed to drip (supplied) the acid in multiple times. For example, by carefully controlling the dripping amount of the acid, or dripping while gradually diluting the acid to make the concentration thinner, the concentration of the sum of the second group VI elements in the base material 16 may be gradually reduced (i.e., continuously changed).
[0197] [Third Embodiment] The light emitting element 2 can be preferably used as a light source of a light emitting device such as a display device or a lighting device. A light emitting device can include at least one light emitting element 2. Hereinafter, the case where the light emitting element 2 is used as a light source of a display device will be described as an example.
[0198] Fig.19 FIG. 2 is a top view showing an example of the structure of a display device according to this embodiment. Fig.19 As shown, the display device 100 includes: a display unit 15 including a plurality of sub-pixels X, and a driving circuit 25 for driving the display unit 15. For example, the sub-pixel X includes the light-emitting element 2 and the pixel circuit 5 described in the first embodiment or the second embodiment. In addition, the display device 100 may also be a lighting device.
[0199] The present disclosure is not limited to the above-mentioned embodiments, and various changes can be made within the scope of the claims. The embodiments obtained by appropriately combining the technical solutions disclosed in different embodiments are also included in the technical scope of the present disclosure. Moreover, by combining the technical means disclosed in each embodiment, new technical features can be formed. Description of Reference Numerals
[0200] 2: Light-emitting element 6: HTL (hole transport layer) 8: EML (Emitting Layer) 10: ETL (Electron Transport Layer) 16: Base material 14: QD (Quantum Dot) 14C: Nuclear 14S: Shell 16H: Halide ion 100: Display device
Claims
1. A light emitting element, characterized in that: It has: a light emitting layer; and a hole transport layer disposed adjacent to the light-emitting layer, The light-emitting layer comprises a base material and a plurality of quantum dots, wherein the base material contains at least one inorganic compound. The parent material includes a parent compound as the inorganic compound, the parent compound having at least one first Group VI element as a main component, and the parent material includes at least one second Group VI element, the period number of the second Group VI element being smaller than the period number of the first Group VI element contained in the parent compound, The concentration of the total of the second group VI elements in the base material is 1×10 16 Atom / cm 3 Above and 1×10 20 Atom / cm 3 Within the following range.
2. The light emitting element according to claim 1, characterized in that The parent compound is a Group II-VI compound.
3. The light emitting element according to claim 1 or 2, characterized in that: The first Group VI element is at least one selected from the group consisting of S, Se, and Te.
4. The light emitting element according to any one of claims 1 to 3, characterized in that The quantum dot has a core and a shell, The shell comprises the same material as the parent compound.
5. The light emitting element according to any one of claims 1 to 3, characterized in that: The quantum dot has a core and a shell, The band gap of the parent material is larger than the band gap of the core or the shell.
6. The light emitting element according to claim 5, characterized in that The band gap of the parent material is larger than the band gap of the shell.
7. The light emitting element according to any one of claims 4 to 6, characterized in that: The average distance between the cores of adjacent quantum dots is greater than 3 nm.
8. The light emitting element according to any one of claims 1 to 7, characterized in that: The second Group VI element is O.
9. The light emitting element according to any one of claims 1 to 8, characterized in that: The concentration of the sum of the first group VI elements in the matrix is 10 greater than the concentration of the sum of the second group VI elements in the matrix. 5 times or more.
10. The light emitting element according to any one of claims 1 to 9, characterized in that: The light-emitting element further includes an electron transport layer, which is disposed adjacent to the light-emitting layer on the side opposite to the hole transport layer across the light-emitting layer. The total concentration of the second Group VI elements in the matrix closer to the hole transport layer than the center of the thickness direction of the light-emitting layer is greater than the total concentration of the second Group VI elements in the matrix closer to the electron transport layer than the center of the thickness direction of the light-emitting layer.
11. The light emitting element according to claim 10, characterized in that The concentration of the total of the second Group VI elements in the base material decreases toward the electron transport layer in the thickness direction of the light emitting layer.
12. The light emitting element according to claim 10 or 11, characterized in that: The total concentration of the second Group VI element in the matrix on the side closer to the hole transport layer than the center in the thickness direction of the light-emitting layer is 1×10 19 Atom / cm 3 Above and 1×10 20 Atom / cm 3 Within the following range, The concentration of the total of the second Group VI elements in the matrix on the side closer to the electron transport layer than the center in the thickness direction of the light-emitting layer is 1×10 16 Atom / cm 3 Above and 1×10 18 Atom / cm 3 Within the following range.
13. The light emitting element according to claim 10, characterized in that The second Group VI element is mixed and present only on the base material on the side closer to the hole transport layer than the center in the thickness direction of the light-emitting layer.
14. The light emitting element according to claim 13, characterized in that: The second Group VI element is mixed and exists within a range of 1 / 2 of the thickness of the light emitting layer.
15. The light emitting element according to any one of claims 1 to 14, characterized in that: The parent material further contains at least one halogen element.
16. The light emitting element according to claim 15, characterized in that The total concentration of the halogen elements in the matrix is 1×10 16 Atom / cm 3 above.
17. The light emitting element according to claim 16, characterized in that The total concentration of the halogen elements in the matrix is 1×10 19 Atom / cm 3 the following.
18. The light emitting element according to any one of claims 15 to 16, characterized in that: The average value of the total concentration of the halogen elements in the region within 1 nm from the outermost surface of each of the multiple quantum dots in the matrix is more than 10% higher than the average value of the total concentration of the halogen elements in the region more than 1 nm from the outermost surface of each of the multiple quantum dots in the matrix.
19. The light emitting element according to any one of claims 1 to 18, characterized in that: The base material contains at least one of Mg and Li.
20. The light emitting element according to any one of claims 1 to 19, characterized in that: The matrix material is filled between the plurality of quantum dots in the light-emitting layer.
21. The light emitting element according to any one of claims 1 to 20, characterized in that: The base material has a continuous film in a plane direction perpendicular to the thickness direction of the light-emitting layer, and the continuous film has a thickness of 1000 nm. 2 Above the area.
22. The light-emitting element according to any one of claims 1 to 21, characterized in that: The plurality of quantum dots are dispersed in the matrix.
23. The light emitting element according to any one of claims 1 to 22, characterized in that: The plurality of quantum dots are contained in the matrix.
24. A display device, characterized in that: The light emitting device comprises the light emitting element according to any one of claims 1 to 23.